DINAMIKA KURIKULUM DI MADRASAH AL-QISMUL ALI AL-WASHLIYAH (1955-2018) - Saiful Akhyar Lubis; Achyar Zein; Debi Mifthaul Khair Harahab (JP : JURNAL PENDIDIKAN, 2021)
This research article aims to explain the dynamics of the curriculum at Madrasah Al-Qismul Ali Jalan Ismailiyah and its relevance to the development of Islamic education today. The research used is qualitative research with a phenomenology study approach. Collecting data using three techniques of interview, observation and documentation. The collected data was then analyzed through three stages, namely reduction, display and verification, then tested for correctness with triangulation techniques. The results of this study are: 1) the dynamics of the curriculum at Madrasah Al-Qismul Ali Medan experienced three periods of change, namely the Al Qismul Ali level curriculum in 1955-1977, the Al Qismul Ali Madrasah level curriculum in 1978-2009, and the Al Qismul Ali Madrasah curriculum. 2012-2013 and is the last curriculum used until now. The relevance of the curriculum at Madrasah Al-Qismul Ali Medan with the development of today's education is to have a vision, mission and educational goals that are in line with the goals of National Education with the hope of creating graduates who are knowledgeable and skilled in religion, science and technology.Keywords: Curriculum, Madrasah, and National Education